2005
DOI: 10.1139/f05-184
|View full text |Cite
|
Sign up to set email alerts
|

An experimental evaluation of competitive and thermal effects on brown trout (Salmo trutta) and Bonneville cutthroat trout (Oncorhynchus clarkii utah) performance along an altitudinal gradient

Abstract: Temperature-mediated competition (i.e., dominance shifts between species depending on temperature) may explain the segregation of salmonid species along altitudinal stream gradients. We evaluated this hypothesis for exotic brown trout (Salmo trutta) and native Bonneville cutthroat trout (Oncorhynchus clarkii utah) by rearing them in experimental sympatry and allopatry using enclosures constructed at six sites spaced along a 45-km segment of a mountain stream. For both species, we compared condition and growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(105 citation statements)
references
References 35 publications
6
98
1
Order By: Relevance
“…Experimental manipulations of two larval anurans, Pelodytes punctatus Daudin and B. bufo, showed that Bufo individuals increased their use of the water column in the presence of the other, while Pelodytes did not change their space use (Richter-Boix et al 2004). Furthermore, the darter Etheostoma zonale (Cope) excluded Etheostoma olmstedi Storer from riZe and run habitats (Grey et al 2005), and exotic brown trout (Salmo trutta L.) displaced cutthroat trout from low-Xow areas in streams (McHugh and Budy 2005). Such eVects of competition may be best observed when new species are introduced, as revealed in our transfer experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental manipulations of two larval anurans, Pelodytes punctatus Daudin and B. bufo, showed that Bufo individuals increased their use of the water column in the presence of the other, while Pelodytes did not change their space use (Richter-Boix et al 2004). Furthermore, the darter Etheostoma zonale (Cope) excluded Etheostoma olmstedi Storer from riZe and run habitats (Grey et al 2005), and exotic brown trout (Salmo trutta L.) displaced cutthroat trout from low-Xow areas in streams (McHugh and Budy 2005). Such eVects of competition may be best observed when new species are introduced, as revealed in our transfer experiment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, native cutthroat trout in the interior West may be relegated to the highest elevation areas in the summer months to find suitable temperatures, and nonnative brown trout may occupy lower elevation habitats because of their tolerance to higher temperatures. An exception in this case may be Bonneville cutthroat trout that appear to occupy similar habitats to brown trout in larger rivers during warmer summertime periods (Colyer and others, 2005;McHugh and Budy, 2005). Where nonnative brook trout occupy similar habitats to cutthroat trout, similar shifts may occur.…”
Section: Climate Change Risk and Small Populationsmentioning
confidence: 95%
“…These mechanisms have been studied extensively in controlled laboratory and field experiments at small scales (see reviews in Fausch 1988, Dunham and others 2002a, Peterson and Fausch 2003b, but results are often difficult to generalize to larger spatial and longer time scales (Rieman and others 2006). An exception is experiments designed to explicitly consider environmental factors like temperature across a range of natural conditions, either in the field (McHugh and Budy 2005) or by simulating conditions in the laboratory (Taniguchi and Nakano 2000).…”
Section: Displacement_of_native_salmonidsmentioning
confidence: 99%